Review of studies on the public–private partnerships (PPP) for infrastructure projects. Issue 5 (July 2018) - Cui, Caiyun; Liu, Yong; Hope, Alex; Wang, Jianping
Abstract: Public–private partnership (PPP) is an approach adopted to enhance the economic value of infrastructure outputs, and it encompasses a broad spectrum of public sector infrastructure. Many researchers have explored the application of PPP to improve the efficiency of infrastructure delivery. This study aims to review the existing PPP research to explore the status quo, trends, and gaps in research for PPP infrastructure projects. A systematic process involving a three-phase word frequency analysis, cluster analysis, and a search on potential research topics helps to provide enough potential articles related to PPP research and reduce arbitrariness and subjectivity involved in the research topic analysis. As a result, six main research topics aligned with the infrastructure PPP projects were derived. The research gaps and research directions can serve as a motivation for researchers and practitioners to work on the next generation of PPP studies to support the development of infrastructure. Highlights: Word frequency analysis and cluster analysis were used to analyse PPP research. Six main research topics about infrastructure PPP projects were derived from 754 articles. Research gaps still exit in flexible contracting, knowledge management and social impact assessment, etc. The findings of this study provide a suggestion of future research directions.